Model Kelembagaan Pemanfaatan Sumber Daya Air Muncul di Kecamatan Banyubiru Kabupaten Semarang - Wungo, Grandy Loranessa; Wahyono, Hadi (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
The phenomenon of the efficient use of water resources, especially with regard to institutional models of Muncul water resources in Banyumanik Subdistrict, Semarang Regency. This is not only caused by the exploitation of water resources by certain parties, then the increase of population, the scarcity of water allocation, and abssortion land reduced. However due to a fact that the regions that have a wealth of water resources has a large degree of coordination between stakeholders is still low and pay attention to the side of sustainability, while welfare their local community is still low. So it needed a formula appropriate institutional model in order for the utilization of Muncul water resources can continue to be used. The research method usedÂ descriptive qualitative methods. The analysis is used are the analysis of the institutional forms, interaction mechanism, things that affect the institutional utilization and analysis of the institutional model of Muncul water resource utilization in Banyumanik Subdistrict, Semarang Regency. Conclusion of this research is because of the the overlap of responsibilities between stakeholders, the form of a cooperation agreement which has not legal laws, the high use of individual water sources during the dry season so that the discharge water is reduced, the lack of community awareness in maintaining sustainability of water resources comes up, the interaction is still shaped the forum coordination and negatively impact for local people it needs to be seriously considered the development of the institutional model of the whole of the relevant parties both Governments, the private and the public to support and facilitate efforts for tackling the problems institutional of Muncul water resource utilization.